RBTT-02. ENHANCING VACCINE RESPONSES WITH DOSE-INTENSIFIED TEMOZOLOMIDE IN GLIOBLASTOMA: INITIATION OF THE I-ATTAC TRIAL. (5th November 2018) - Batich, Kristen; Ashley, David; Archer, Gary; Sanchez-Perez, Luis; Norberg, Pam; Congdon, Kendra; Herndon, James; McSherry, Frances; Gemberling, Sarah; Hesler, Rachel; Jaggers, Denise; Van, Rachael; et al.
Abstract: Two of our previous clinical trials targeting Cytomegalovirus (CMV) protein pp65 in newly diagnosed glioblastoma (GBM) using pp65-specific dendritic cell (DC) vaccines have yielded long term survival rates greatly exceeding those predicted with standard of care. In the ATTAC trial (IND 12839), patients received sequential DC vaccination throughout monthly cycles of standard temozolomide (STD-TMZ) 200mg/m 2 /d for 5d and were randomized to one of two vaccine site preconditioning regimens. Significantly higher rates of DC migration (p=0.04) and survival (p=0.013) were observed in patients randomized to tetanus preconditioning, with half of the cohort living to nearly five years after diagnosis. In the ATTAC-GM trial, we treated a subsequent cohort with dose-intensified TMZ (DI-TMZ) 100mg/m 2 /d for 21d prior to and throughout vaccination with GM-CSF-containing DC vaccines and observed extraordinarily prolonged progression-free survival (PFS) and overall survival (OS) (median 25.3 and 41.1 months, respectively). In this trial, DI-TMZ-induced lymphopenia facilitated homeostatic expansion of pp65 responses after an initial DI-TMZ cycle but later ablated T cell responses when monthly cycles were reintroduced. The benefit of DI-TMZ thus warrants further study in a larger series of patients. Here we describe the initiation of a validation trial, "I-ATTAC: Improved Anti-Tumor Immunotherapy Targeted Against Cytomegalovirus in Patients with Newly-Diagnosed WHO Grade IV Unmethylated Glioma" (IND-16301). This prospective single arm Phase 2 trial of 48 patients will validate our findings that tetanus preconditioning and GM-CSF in conjunction with pp65-DCs extends OS in patients with newly diagnosed, unmethylated GBM. By withholding additional TMZ cycles in this patient population, we hypothesize that CMV immune responses will not be abrogated as previously observed, and that this greater expansion will translate into further prolonged survival (primary objective). A series of secondary objectives will be evaluated for the association between increased DC migration, systemic mediators of tetanus preconditioning, and T cell polyfunctionality with survival.